2013
DOI: 10.1063/1.4816290
|View full text |Cite
|
Sign up to set email alerts
|

The streamwise drag-reduction response of a boundary layer subjected to a sudden imposition of transverse oscillatory wall motion

Abstract: A DNS study is presented, which examines the response of a spatially developing boundary layer to oscillatory spanwise wall motion imposed over a limited streamwise stretch. At the heart of the study is the dependence of the streamwise variations in skin friction and turbulence properties on the period of the oscillatory motion, with particular emphasis placed on the behaviour downstream of the start of the actuation. The friction Reynolds number just upstream of the actuation is Re τ = 520, and the wall-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 24 publications
5
44
0
Order By: Relevance
“…As already mentioned, no Reynolds number effect was observed in the boundary-layer experiment of Ricco & Wu (2004). Numerical simulations of the turbulent boundary layer with wall oscillation have been performed in a few studies (Yudhistira & Skote 2011;Skote 2012;Lardeau & Leschziner 2013). A drag reduction of DR = 29.4% was obtained at Re θ = 500 (or Re τ = 260) for A + = 12 and T + = 132 (Skote 2012).…”
Section: Reynolds Number Effectmentioning
confidence: 80%
See 3 more Smart Citations
“…As already mentioned, no Reynolds number effect was observed in the boundary-layer experiment of Ricco & Wu (2004). Numerical simulations of the turbulent boundary layer with wall oscillation have been performed in a few studies (Yudhistira & Skote 2011;Skote 2012;Lardeau & Leschziner 2013). A drag reduction of DR = 29.4% was obtained at Re θ = 500 (or Re τ = 260) for A + = 12 and T + = 132 (Skote 2012).…”
Section: Reynolds Number Effectmentioning
confidence: 80%
“…In these numerical studies, a single Reynolds number was used, making a direct comparison for the Reynolds number effect between different studies less straightforward. Comparing Skote (2012) and Lardeau & Leschziner (2013) gives a change of ∆DR = 4.4% between Re τ = 260 and Re τ = 520, but it should be noted that different T + values were used in their simulations. Skote (2012) compared his boundary-layer DNS results at Re θ = 500 with channel flow data available in literature using an equivalent Re θ numbers for the channel flow.…”
Section: Reynolds Number Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific case of spanwise-forcing techniques for drag reduction includes the wellknown spanwise-oscillating wall (Jung et al 1992) and its generalizations made by the spanwise-travelling waves (Du et al 2002) and streamwise-travelling waves (Quadrio et al 2009); although most of the available information concerns internal flows, numerical experiments (Skote 2011;Lardeau & Leschziner 2013;Skote 2013;Mishra & Skote 2015) have shown that the forcing is effective in external flows too. The streamwise-travelling waves, in particular, yield larger maximum drag reduction and, more importantly, improved energetic efficiency, which is essential if drag reduction is motivated by the need to save energy.…”
Section: Introductionmentioning
confidence: 99%